Conservation of the Nuclear Receptor Response Element in HIV-1 LTRs: A Possible PPAR Response Element?. (18th May 2013) - Hurst, Tara
Abstract : Infection with HIV-1 continues to be a threat to public health. Successful antiretroviral therapy has reduced the risk of developing AIDS but cannot fully eradicate the virus due to latent proviral sequences remaining in infected cells. The 5′-long terminal repeat (LTR) of HIV-1 is critical for the regulation of transcription of the viral RNA and subsequent production of new viral particles. Indeed, the regulation of transcription relies upon the binding of host cell transcription factors and associated regulatory proteins to the LTR. Recently, it has been found that the treatment of cells with ligands of a number of nuclear receptors (NRs) resulted in inhibition of HIV-1 replication. This inhibition likely occurs via effects on other proteins that bind to the 5′-LTR, notably NF- κ B. Here, the possible binding site of one NR, the peroxisome proliferator-activated receptor (PPAR), in the HIV-1 5′-LTR is analysed within isolates of the virus. Given the high mutation rate of HIV-1, it is striking that this region remains conserved in more recent isolates from geographically distinct regions. This work provides a rationale for further study of the binding site recognised by PPAR in the HIV-1 5′-LTR.